Pelatihan Mitigasi Bencana Berbasis Bel Getar untuk Meningkatan Kesiapsiagaan Civitas Akademika Sekolah Tunarungu di SLB/B Dena Upakara Wonosobo: Vibrating Bell-Based Disaster Mitigation Training to Improve Disaster Preparedness among the Academic Community of SLB/B Dena Upakara Wonosobo - Fifi Ariana Himawan; Maryana Maryana; Aly Sahid Saifullah; Muhammad Abdul Halim Ar-Rasyid; Maleva Dika Nur Kholifah (Poltekkes Kemenkes Yogyakarta, 2025)
Wonosobo Regency is a disaster-prone area with a high risk of natural hazards, while SLB/B Dena Upakara, a school for students with hearing disabilities, previously lacked an inclusive and accessible disaster mitigation system. Limited access to audio-based warning information places deaf students among the most vulnerable groups during disasters, highlighting the need to strengthen disaster preparedness through an adaptive emergency response system. This community service program aimed to improve the knowledge, preparedness, and disaster response skills of the academic community at SLB/B Dena Upakara Wonosobo in facing earthquake disasters through education, evacuation simulations, and the implementation of a vibrating bell as an early warning device. The intervention employed a participatory training and mentoring approach consisting of disaster mitigation education, introduction to disaster response standard operating procedures (SOPs), emergency response simulations, and vibrating bell implementation. The program was conducted from June to September 2023 and involved 97 participants, including 89 deaf students and 8 teachers. Evaluation was carried out using pre-tests, post-tests, and observation of participants’ skills during evacuation simulations. The results demonstrated an improvement in participants’ understanding of self-rescue procedures, evacuation routes, and the use of vibrating bells as a disability-friendly early warning system. All participants acknowledged the importance of developing disaster mitigation SOPs and evacuation pathways within the school environment and actively participated throughout the training and simulation activities. This program was effective in enhancing disaster literacy and preparedness among the school academic community, thereby supporting the creation of a safer, more inclusive, and disaster-responsive school environment.